Diagnosis of asbestos-related lung diseases. (4th March 2019) - Harris, Edward J. A.; Musk, Arthur; de Klerk, Nicholas; Reid, Alison; Franklin, Peter; Brims, Fraser J. H.
ABSTRACT: Introduction : The diagnosis of lung disease in asbestos-exposed individuals is a process that not only requires a detailed occupational and tobacco smoking history, but the correlation with physical signs, appropriate imaging, detailed lung function assessment and histology/cytology when required. Worldwide, the total quantity of asbestos mined is static, having decreased dramatically in developed countries but increased in countries where there is no restriction on mining: for example, Russia, China, Brazil, and Kazakhstan. The predominant diagnostic challenge in most cases of possible asbestos-related disease is the significant interval between exposure and development of the disease. Also challenging is the estimation of an individual's risk of disease, not least because asbestos-induced malignancy can be rapidly fatal, and, in the case of lung cancer, early detection can lead to treatment with curative intent. Areas covered : Discussion of quantitative asbestos exposure estimation and risk assessment, selection of the most appropriate imaging modality and frequency of imaging. Expert commentary : Consideration of the future for asbestos-related lung disease includes screening those at highest risk particularly in relation to ongoing mining operations and the management of in-situ asbestos. In the future, screening programs designed with estimation of risk of malignancy, based on quantitative estimates of asbestos exposure, and smoking history are indicated.